Structural organization of pobitovogo increase and division of codes of gold proportion - Азаров, О. Д.; Черняк, О. І. (Problems of Informatization and Control, 2007)
The features of structural organization and functioning of devices are considered for a pobitovogo increase and division of codes of gold proportion. Devices are offered for a pobitovogo increase and partaking with the diminished charges of vehicles. The diagrams of sentinels of work of devices are resulted